Laying performance, egg quality and hatchability traits of Japanese quail (coturnix coturnix japonica) fed a chromium yeast feed additive Layplus(R): Effect of Leptidinia reticulata on female quails - Oyebanji, BO; Atoki, FT (Bangladesh Journal of Animal Science, 2018)
A 12-week study was conducted at the Teaching and Research Farm of the Obafemi Awolowo University, Ile-Ife to evaluate the effect of dietary inclusion of LAYPLUS® (LP) on fertility and egg parameters of female Japanese quails, Coturnix coturnix japonica. Two hundred and ten birds of average weight of 167.75±3.94g were used for this study, and they were allocated randomly into seven treatment groups and replicated thrice. Group 1 served as control without inclusion of LAYPLUS®, while groups 2, 3, 4 and 5 had 250 mg/kg, 500 mg/kg, 750mg/kg and 1000mg/kg inclusion of LP and group 6 had 240mg/kg of vitamin E, respectively, and group 7 clomiphene citrate. Eggs were collected daily and egg production was calculated on a bird-day basis. The data obtained were analyzed using one-way ANOVA. There was significant increase (p<0.05) in the egg production parameters namely egg weight, egg laid per hen and percentage laying rate of LP500mg/kg compared with other groups. The highest percentage egg production was by the LP500mg/kg at 57% while the lowest was by the LP250mg/kg at 41%. There was no significant difference in the egg weight and Haugh unit among the supplemented birds and the control group. There was significant difference among the treatments in the percentage hatchability of the eggs with LP500mg/kg eggs recording the highest value of 95.68%. It can be concluded from this experiment that supplementation of the feed with LP at 500mg/kg had beneficial effect on quail production through improved effect on egg production and hatchability. Bang. J. Anim. Sci. 2018. 47 (2):68-75